2023
DOI: 10.1007/s11104-023-05969-w
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fertilizers for Citrus production: assessing nutrient supply via fertigation or foliar application

Abstract: Background and AimsCitrus trees are severely affected by zinc (Zn) de ciency, which impairs plant growth and fruit yield. Zn fertilization is usually recommended in eld orchards, and application strategies toward nutrient use e ciency are key for successful crop management. MethodsField studies were carried out with sweet orange trees for four growing seasons, testing Zn (nitrate, sulfate or EDTA) applied either via fertigation or foliar spray compared to a control without Zn. ResultsThe Zn concentrations in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Assessing zinc absorption of three different fertilizers (ZnSO4.7H2O, Zn(NO3)2, and Zn-EDTA) via foliar fertilization on citrus trees for 4 years, Boaretto et al (2023) demonstrated that nitrates were +113% and +214% more efficient than sulfate and EDTA, respectively. These authors had to decrease the concentration of zinc nitrate applied to plants to half of the dose used in the fourth year of the experiment due to leaf scorching.…”
Section: Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…Assessing zinc absorption of three different fertilizers (ZnSO4.7H2O, Zn(NO3)2, and Zn-EDTA) via foliar fertilization on citrus trees for 4 years, Boaretto et al (2023) demonstrated that nitrates were +113% and +214% more efficient than sulfate and EDTA, respectively. These authors had to decrease the concentration of zinc nitrate applied to plants to half of the dose used in the fourth year of the experiment due to leaf scorching.…”
Section: Sourcementioning
confidence: 99%
“…While chlorine-based fertilizers are known for their efficiency in providing nutrients to plants through foliar fertilization (Guedes, 2012;Fu et al, 2016;Boaretto et al, 2023), they are not commonly used for this purpose. But why?…”
Section: The Drawbacks Of Chlorine-based Fertilizers To Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is particularly successful in irrigating salty soil. The primary function of the performance is as follows [7][8][9][10][11][12]:…”
Section: Introductionmentioning
confidence: 99%